Reading with feeling the aesthetics of appreciation - Feagin, Susan L. 1948- (Cornell Univ. Press, 1996)
Feelings and other affective responses to a work of fictional literature are an important part of appreciation, and the capacity to inspire such responses is part of what is valuable about literary works of art. Susan L. Feagin's philosophical exploration of appreciation, focusing specifically on its emotional or affective components, asks us to consider aesthetic appreciation as getting the value out of the work. Appreciation involves exercising abilities. Feagin develops a psychological model for understanding how one becomes emotionally engaged with something one knows is fictional. She stresses the importance of the role of imagination in producing affective responses. Imagination is harnessed by the writer's choice of phrase or depiction of detail. Feagin cites the work of Angela Carter, Molly Keane, Heinrich Boll, and Gabriel Garcia Marquez and draws an extended example from Henry James.
Includes bibliographical references and index
Keywords: Critique littéraire; Emoties; Esthetica; Literatuurreceptie; Ästhetik; Reader-response criticism; Leser; Rezeption; Epik